2021
DOI: 10.1093/eurjpc/zwab061.372
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodelling in a large cohort of strength competitive athletes: not so common and differs by sex

Abstract: Funding Acknowledgements Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This research was supported by FMBA of Russia Background. There are still very limited data about physiological cardiac adaptation in strength athletes.  Purpose. To describe structural and functional features of left ventricular (LV) in a large cohort of healthy strength athletes. Methods. A total of 673 Caucasian athletes (we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…A study of a total of 1083 combat sports athletes (males, n=639; females, n=444), found significantly lower LVM and RWT values in females than in male athletes, which matches our findings 10 . Furthermore, our data is inconsistent with previous research from 2021, conducted on a sample of 200 men and 78 women in weightlifting and various martial arts, which showed that female athletes were significantly more likely to have an eccentric type of hypertrophy than men who were more likely to have concentric remodeling of the LV 19 . The adaptations involve the entire cardiovascular system, particularly in athletes, LV root remodeling can also be expected due to the hemodynamic load caused by intensive training 22 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study of a total of 1083 combat sports athletes (males, n=639; females, n=444), found significantly lower LVM and RWT values in females than in male athletes, which matches our findings 10 . Furthermore, our data is inconsistent with previous research from 2021, conducted on a sample of 200 men and 78 women in weightlifting and various martial arts, which showed that female athletes were significantly more likely to have an eccentric type of hypertrophy than men who were more likely to have concentric remodeling of the LV 19 . The adaptations involve the entire cardiovascular system, particularly in athletes, LV root remodeling can also be expected due to the hemodynamic load caused by intensive training 22 .…”
Section: Discussioncontrasting
confidence: 99%
“…The literature has already established that judokas, regardless of gender, have a significantly higher RWT and greater left ventricular mass than non-athletes of the same gender 17 , however the cardiac remodeling is complex and depends on various factors 18 . The results obtained are in line with research conducted to date, which indicate that gender is a significant factor that has an important influence on the change of heart geometry in athletes 19 20 . Whyte et al 21 conducted a survey of judokas, including 17 male and 14 female athletes, and 11 participants in the control group.…”
Section: Discussionsupporting
confidence: 90%